Constants Rule

Find the constant term in the expansion of ( x 2 + 1 x ) 12 . \large \left(x^2 + \frac{1}{x}\right)^{12}.

567 549 564 495

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Hana Wehbi
Jun 9, 2016

According to the binomial theorem: ( x 2 + 1 x ) 12 = k = 0 12 ( 12 k ) ( x 2 ) k ( 1 x ) 12 k \Large(x^{2}+ \frac{1}{x})^{12} = \sum_{k=0}^{12}{12\choose k}(x^{2})^{k}(\frac{1}{x})^{12-k}

( x 2 + 1 x ) 12 = k = 0 12 ( 12 k ) ( x ) 3 k 12 \Large(x^{2}+ \frac{1}{x})^{12}= \sum_{k=0}^{12}{12\choose k}(x)^{3k-12} ;

Set: 3 k 12 = 0 k = 4 \large 3k-12=0 \implies k=4 ;

Thus, the constant term is ( 12 4 ) = 495 \Large {12\choose 4} = \boxed{495}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...